The Role of E-Government, Financial Audits, and Internal Control Systems in Enhancing Government Performance Accountability - Yola Sri Ratna Alfiyani; Azas Mabrur (IPSAR (International Public Sector Accounting Review), 2025)
This study aims to analyze the empirical influence of the Electronic-Based Government System, audit opinions, and the maturity level of the Government Internal Control System on the Government Performance Accountability. The Electronic-Based Government System implementation is measured using the SPBE index, audit opinions are assessed through the transformation of financial audit opinion scales, and AKIP performance accountability is proxied by its predicate. Using ordinal logistic regression, this research examines 384 Ministries/Agencies during the 2018–2022 period, with data processed through SPSS 28.0. The findings reveal that higher SPBE index scores, Unqualified audit opinions, and advanced SPIP maturity significantly increase the likelihood of achieving better AKIP ratings. The novelty of this study lies in its comprehensive analysis of SPBE implementation and SPIP maturity using the latest dataset (2018–2022) across Ministries/Agencies. These results underscore the strategic importance of digital governance, reliable financial reporting, and robust internal control systems in improving institutional performance accountability.